The Contribution of Nitrate Dissimilation to Nitrate Consumption in narG- and napA-Containing Nitrate Reducers with Various Oxygen and Nitrate Supplies - Xing Chen; Chunmei Liu; Baoli Zhu; Wenxue Wei; Rong Sheng (Microbiology Spectrum, 2022)
ABSTRACT Nitrate reducers containing narG or napA play an important role in the nitrogen cycle, but little is known about their functional differentiations in relation to environmental changes. In this study, three types of nitrate reducers in the genus Pseudomonas, including strains containing narG (G type), napA (A type) and both narG and napA (GA type), were selected to explore their functional performances under varied nitrate and oxygen concentrations. Their growth characteristics, nitrate consumption, and dissimilatory nitrate-reducing activity were investigated. Growth and nitrate consumption of all three types of strains were generally promoted with increasing oxygen and nitrate concentrations. However, their dissimilatory nitrate-reducing activities were restricted by oxygen supply. When supplied with 0.25 mM KNO3, A-type strains showed a higher growth rate but lower activity of dissimilatory nitrate reduction (DNR) than G-type strains, regardless of oxygen concentration. However, when nitrate concentration increased to 0.75 mM or 5 mM, G-type strains displayed stronger capability of nitrate consumption and DNR than A-type strains under anaerobic conditions, whereas under oxygenated conditions, A-type strains exhibited higher growth and nitrate consumption but weaker DNR than G-type strains. The GA-type strains appeared similar to G type under anaerobic conditions but performed more similarly to A type in aerobic environments. In summary, the nitrate consumption of narG-containing nitrate reducers is mainly caused by DNR in both anaerobic and aerobic environments, while the large proportion of nitrate consumption in A-type nitrate reducers under the aerobic condition is attributed to the assimilation by cell growth. IMPORTANCE Nitrate reducers containing narG or napA are ubiquitous, but little is known about their functional performance in various environments. Our study provides an important clue that the nitrate consumption of narG-containing strains is mainly caused by dissimilatory reduction in the environments, while that of napA-containing nitrate reducers under anaerobic conditions is ascribed to nitrate dissimilation but under the aerobic condition is attributed to the assimilation by cell growth. This finding broadens the understanding of aerobic nitrate reduction in the nitrogen cycle and highlights the important role of narG-containing bacteria in nitrate reduction under aerobic conditions.